Foreign outsourcing collaboration within a developing economy’s perspective: A case of the Pakistani textile industry - Ali, Irfan; Mahmood, Zafar (PloS one, 2024)
This paper develops an outsourcing collaboration model from a firm’s perspective operating in a developing economy. The model considers that producers of the final goods residing in a developed country, and operators of manufacturing plants in a developing country collaborate with each other. The final goods producer supplies headquarter services for the production of intermediate goods in the developing country. The operators of manufacturing plants also supply their services in the domestic economy. This arrangement leads to foreign outsourcing collaborations (FOC) between firms of developed country and developing country. The operators of manufacturing plant maximize revenue subject to the cost constraint. The first order conditions suggests that an increase in wages of skilled labor, price of domestic inputs, and cost of production deter FOC. On the other hand, an increase in demand for and price of foreign headquarter services increases the FOC. Empirical analysis based on data collected from 217 clothing (textile and apparel) firms in the city of Faisalabad (Pakistan) reveals that an increase in wage to labor-productivity ratio reduces FOC. An improvement in skilled of the labor and foreign headquarter services give rise to FOC, whereas an increase in economies-of-scope enhances FOC. Additionally, an inverted U-shaped relationship is found between the cost of production and FOC, which shows that at the initial stage, the firm’s cost of production increases with an increase in the level of FOC, but soon after the tipping point, the firm’s cost starts decreasing with a further increase in FOC.